1999
DOI: 10.1149/1.1391816
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Hydrogen/Water Mixtures on Nickel‐Zirconia Cermet Electrodes: I. DC Polarization Characteristics

Abstract: The reaction of hydrogen/water mixtures on nickel‐zirconia cermet electrodes has been investigated as a function of potential and temperature at three different partial pressures of the reactants. Apparent kinetic parameters, namely, reactions orders, activation enthalpies, and pre‐exponential factors, were determined as a function of potential in low‐temperature (725–845°C) and high‐temperature (845–950°C) regions for both the hydrogen oxidation and the hydrogen evolution reactions. In the low‐temperature reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 8 publications
9
59
0
Order By: Relevance
“…The charge transfer coefficients are assumed to be constant within the discussed temperature range. This assumption is consistent with the experimental data reported by Holtappels et al [29]. Constant temperatures are assumed within the computational domain, and the transport coefficients are approximated to be constant in relation to the model variables.…”
Section: Mathematical Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…The charge transfer coefficients are assumed to be constant within the discussed temperature range. This assumption is consistent with the experimental data reported by Holtappels et al [29]. Constant temperatures are assumed within the computational domain, and the transport coefficients are approximated to be constant in relation to the model variables.…”
Section: Mathematical Modelsupporting
confidence: 84%
“…It is assumed that in the above presented set of equations the anodic forward charge transfer coefficient α an,fwd = 1.4 and the anodic backward reaction coefficient α an,bcw = 0.6, as was experimentally measured by Holtappels et al [29]. The charge transfer coefficients are assumed to be constant within the discussed temperature range.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In SOFC modeling studies, the coefficient is generally assumed to be 0.5 (symmetric Butler-Volmer equation), primarily due to the lack of experimental data [26]. However, detailed electrochemical kinetic studies [26][27][28][29] on Ni pattern anodes or Ni cermet anodes has shown that the charge transfer coefficient can have values different from 0.5. For example, the charge transfer coefficient, α, for hydrogen oxidation on Ni/YSZ anodes was estimated to be 0.6-0.7 by Utz et al [26] and approximately 0.7 by Holtappels et al [29].…”
Section: Governing Equations and Reaction Kineticsmentioning
confidence: 99%
“…Moreover, even for exclusive H 2 fuel, the anode reaction processes are still a matter of controversy and some reaction models have been proposed. [12][13][14][15][16][17][18][19][20][21] To reveal the reaction process in the Ni-ScSZ anode for hydrocarbon fueled SOFCs, electrochemical measurement and outlet gas analysis were carried out for the H 2 -H 2 O system and hydrocarbons of methane ͑CH 4 ͒, propane ͑C 3 H 8 ͒, n-octane ͑C 8 H 18 ͒, and n-dodecane ͑C 12 H 26 ͒ with S/C = 2.0 for the Ni-ScSZ anode at 1073 K. From results, the following points are discussed: ͑i͒ similarity of anode reaction process between hydrocarbon fuels and H 2 , ͑ii͒ electrochemical anode reaction process, and ͑iii͒ hydrogen producing reaction process.Finally, a simple reaction mechanism is proposed that consistently describes processes in both hydrocarbon fuels and H 2 -fed SOFCs. …”
mentioning
confidence: 99%